Colonic Inhibition of Phosphatase and Tensin Homolog Increases Colitogenic Bacteria, Causing Development of Colitis in Il10-/- Mice. Issue 8 (18th May 2018) - Mitchell, Jonathon; Kim, Su Jin; Koukos, Georgios; Seelmann, Alexandra; Veit, Brendan; Shepard, Brooke; Blumer-Schuette, Sara; Winter, Harland S; Iliopoulos, Dimitrios; Pothoulakis, Charalabos; Im, Eunok; Rhee, Sang Hoon
Abstract: Background: Phosphatase and tensin homolog (Pten) is capable of mediating microbe-induced immune responses in the gut. Thus, Pten deficiency in the intestine accelerates colitis development in Il10 -/- mice. As some ambient pollutants inhibit Pten function and exposure to ambient pollutants may increase inflammatory bowel disease (IBD) incidence, it is of interest to examine how Pten inhibition could affect colitis development in genetically susceptible hosts. Methods: With human colonic mucosa biopsies from pediatric ulcerative colitis and non-IBD control subjects, we assessed the mRNA levels of the PTEN gene and the gene involved in IL10 responses. The data from the human tissues were corroborated by treating Il10 -/-, Il10rb -/-, and wild-type C57BL/6 mice with Pten-specific inhibitor VO-OHpic. We evaluated the severity of mouse colitis by investigating the tissue histology and cytokine production. The gut microbiome was investigated by analyzing the 16S ribosomal RNA gene sequence with mouse fecal samples. Results: PTEN and IL10RB mRNA levels were reduced in the human colonic mucosa of pediatric ulcerative colitis compared with non-IBD subjects. Intracolonic treatment of the Pten inhibitor induced colitis in Il10 -/- mice, characterized by reduced body weight, marked colonic damage, and increased production of inflammatory cytokines, whereas Il10rb -/- and wild-type C57BL/6 mice treated with the inhibitor did not develop colitis. Pten inhibitor treatment changed the fecal microbiome, with increased abundance of colitogenic bacteria Bacteroides and Akkermansia in Il10 -/- mice. Conclusions: Loss of Pten function increases the levels of colitogenic bacteria in the gut, thereby inducing deleterious colitis in an Il10-deficient condition.